Traditional and mediatized soccer fanship: the case of Indonesian Juventus' supporters. (3rd April 2019) - Ferrari, Sara
Abstract : Sports fanship in the contemporary era is increasingly emerging in the virtual space represented by social networks, forums and blogs. This aspect, correlated with the globalization of TV sports broadcasting, conveys a rupture of the traditional fanship connotations, often related to the geographic-familiar context and the local identity, as a primary form of sympathy between a club and its supporters. A relevant aspect of the globalized forms of fanship is represented by groups of supporters who are using the technological communication networks to create original forms of support, which are, in the case of Indonesian Juventus's supporters, an imitation of the local practices, as chants and banners that characterize the stadium terraces. This article analyses the Indonesian fanship for the Italian football club Juventus which is explicative of the dynamics between local and global, traditional and mediatized forms of fanship and their expressions.